A configurational analysis of firms' environmental innovation: Evidence from China's key pollutant‐discharge listed companies. (19th April 2022) - Liao, Zhongju; Zhu, Xiang
Abstract: A firm's environmental innovation behavior results from the interdependence and interaction of multiple factors, and the antecedent conditions are multiple and concurrent. From the perspective of configuration, this study integrates institution theory, stakeholder theory, and strategic management theory, and uses a fuzzy set qualitative comparative analysis (fsQCA) to investigate the combinations of paths that drive firms' environmental innovation. The results revealed that the basic resource capacity of a firm was the basis for environmental innovation, and the role of institution‐ and market‐level factors in driving a firm's environmental innovation requires the support of the firm's resources. The different factors at these three levels—firm, market, and institution—do not contribute equally to a firm's environmental innovation under all conditions; based on a firm's individual resources, the models that drive a firm's environmental innovation can be categorized as market‐driven, institution‐driven, and dual‐stressed.